Football Passing Training Model Based on Game for Children (10-12 Years) - Chandra Prima Sakti; Nofi Marlina Siregar; Iman Sulaiman (Gladi : Jurnal Ilmu Keolahragaan, 2023)
The purpose of this study was to produce game based football passing training model for kids (10-12 years olds) that can be applied in the exercise as well as football school or football club. This training model is expected to help trainers during the training session, especially in passing material. This study uses the ADDIE method. The result of the study resulted in a product in the form of game based football passing training model for kids (10-12 years olds) that was validated by three football experts as many as 8 models of ball possession method. Data were collected through documentation, interviews, and observations. Data analysis was carried out by descriptive qualitative and quantitative methods. The result of the study were in the form of a game based football passing training model book for kids (10-12 years olds). The football passing training model can effectively improve the football passing skill of the kids athlete at the football school or football club. Based on the results of the study, it is proven that the football passing training model for kids (10-12 years olds) has been declared valid and effective and can be applied to kids (10-12 years olds).